PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Ewaldo Evan Thosen; Elizabeth Sugiarto Dermawan (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to analyze and obtain empirical evidence regarding the effects of profitability, leverage, liquidity and firm size on dividend policy. This research was conducted using a purposive sampling method with a total sample of 94 data from manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 3 years, 2018–2020. This research was conducted using secondary data obtained from the financial statements contained on the website www.idx.com. The results obtained from the study concluded that the profitability variable has a positiveand insignificant effect on dividend policy, leverage has a negative and insignificant effect on dividend policy, liquidity has a positive and insignificant effect on dividend policy and firm size has a positive and significant effect on dividend policy.